Nanostructured scaffolds for bone tissue engineering1. Issue 8 (1st February 2013) - Li, Xiaoming; Wang, Lu; Fan, Yubo; Feng, Qingling; Cui, Fu‐Zhai; Watari, Fumio
Abstract: It has been demonstrated that nanostructured materials, compared with conventional materials, may promote greater amounts of specific protein interactions, thereby more efficiently stimulating new bone formation. It has also been indicated that, when features or ingredients of scaffolds are nanoscaled, a variety of interactions can be stimulated at the cellular level. Some of those interactions induce favorable cellular functions while others may leads to toxicity. This review presents the mechanism of interactions between nanoscaled materials and cells and focuses on the current research status of nanostructured scaffolds for bone tissue engineering. Firstly, the main requirements for bone tissue engineering scaffolds were discussed. Then, the mechanism by which nanoscaled materials promote new bone formation was explained, following which the current research status of main types of nanostructured scaffolds for bone tissue engineering was reviewed and discussed. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.